Pengaruh Kelompok Referensi dan Harga Terhadap Keputusan Pembelian HP Xiaomi di Xiaomi Store MOG Kota Malang - Muhammad Alfan Faidzin; Joko Samboro (Ebisnis Manajemen, 2025)
This research is a quantitative descriptive research by using purposive sampling technique. The data are obtained from 100 respondents who use Xiaomi products and have made purchases at the Xiaomi store MOG Malang City. For data analysis, this research uses multiple linear regression analysis. The results of multiple linear regression analysis indicate that the reference group and price variables have a positive effect on purchasing decisions. The results of the F test show that the reference group and price variables have a simultaneous effect on purchase decisions. The results of the T test show that the reference group has a partial effect on the purchase decision and also the price has a partial effect on the purchase decision. Based on this research, it can be concluded that the reference group and price have a positive effect on purchasing decisions. It is suggested that the brand can carry out various kinds of promotion so that they can be accepted by all groups such as parents, not only teenagers. Besides, the brand can maintain their low prices but at the same time good quality that make customers want to buy Xiaomi cell phone products.